SIKAP TERHADAP MUSIK DANGDUT - Clara Moningka; Dina Argitha; Gretha Gretha (Universitas Bunda Mulia, 2014)
Dangdut has become one of Indonesia iconic music. This music is the result of a blend of music from India with Melayu music. The distinctive feature lies in the melody of dangdut who came from music instruments; tabla (a type of percussion instrument that produces sound like